AN INTRODUCTION TO THE THEORY OF DIFFERENTIABLE STRUCTURES ON INFINITE INTEGRAL DOMAINS (Journal of Sciences, Islamic Republic of Iran)
A special class of differentiable functions on an infinite integral domain which is not a field is introduced. Some facts about these functions are established and the special case of z is studied in more detail